Weathering and transport of chromium and nickel from serpentinite in the Coast Range ophiolite to the Sacramento Valley, California, USA. (October 2015) - Morrison, Jean M.; Goldhaber, Martin B.; Mills, Christopher T.; Breit, George N.; Hooper, Robert L.; Holloway, JoAnn M.; Diehl, Sharon F.; Ranville, James F.
Highlights: Cr and Ni in valley soils result from weathering and transport of ultramafic sources. The primary source of Ni is serpentine and the primary source of Cr is chromite. Transport of chromite has a significant effect on the mobility of Cr. Cr and Ni are incorporated into secondary clay and Fe (hydr)oxide minerals and Ni also in Mn (hydr)oxides. Cr(III) from chromite may be the source of Cr(VI) generation in regional groundwater. Abstract: A soil geochemical study in northern California was done to investigate the role that weathering and transport play in the regional distribution and mobility of geogenic Cr and Ni, which are both potentially toxic and carcinogenic. These elements are enriched in ultramafic rocks (primarily serpentinite) and the soils derived from them (1700–10, 000 mg Cr per kg soil and 1300–3900 mg Ni per kg soil) in the Coast Range ophiolite. Chromium and Ni have been transported eastward from the Coast Range into the western Sacramento Valley and as a result, valley soil is enriched in Cr (80–1420 mg kg −1 ) and Ni (65–224 mg kg −1 ) compared to median values of U.S. soils of 50 and 15 mg kg −1, respectively. Nickel in ultramafic source rocks and soils is present in serpentine minerals (lizardite, antigorite, and chrysotile) and is more easily weathered compared to Cr, which primarily resides in highly refractory chromite ([Mg, Fe 2+ ][Cr 3+, Al, Fe 3+ ]2 O4 ). Although the majority of Cr and Ni in soils are in refractory chromite and serpentine minerals, the etching and dissolution of these minerals, presence of Cr- and Ni-enriched clay minerals and development of nanocrystalline Fe (hydr)oxides is evidence that a significant fractions of these elements have been transferred to potentially more labile phases.